Economic Costs of Cardiovascular Diseases in Poland Estimates for 2015–2017 Years - Mela, Aneta; Rdzanek, Elżbieta; Poniatowski, Łukasz A.; Jaroszyński, Janusz; Furtak-Niczyporuk, Marzena; Gałązka-Sobotka, Małgorzata; Olejniczak, Dominik; Niewada, Maciej; Staniszewska, Anna (Frontiers in Pharmacology, 2020)
Background Cardiovascular diseases are associated with growing public and private expenditure on healthcare regardless geographic region. Therefore, it is necessary to accurately estimate the overall societal costs—both direct and indirect expenses from the perspective of patients, caregivers and employers. Research Design The aim of this paper is to determine the direct and indirect costs related to cardiovascular diseases in Poland from 2015 to 2017. All costs are estimated based on data available in the public domain and obtained from the major Polish institutions. Indirect costs were calculated using a modified human capital approach. Results The financial burden of cardiovascular diseases in Poland is significant. This study revealed that total costs (direct and indirect) of cardiovascular diseases, for 2015–2017, range from 34.9 bn PLN (8.2 bn EUR) to over 40.9 bn PLN (9.6 bn EUR). Total direct cost and indirect costs were approximately 6.1 bn PLN (1.4 bn EUR) (16%) and 31.3 bn PLN (7.3 bn EUR) (84%), respectively. Conclusion Collectively, the estimated direct and indirect cost of cardiovascular diseases provide a useful input for economic impact assessments of public health programs and health technology analyses.